Enhancing optical absorption and efficiency of perovskite solar cells using embedded ag nanoparticles array and ITO moth-eye anti-reflective layers - Peng, Qiong; Muhammad Zaheer, Sahibzada; Li, Jingfeng; Rehman, Javed; Shafiee, Saiful Arifin; Masood, M. Kashif; Salem Alsaiari, Norah (Springer Nature, 2026)
Optical loss is a significant factor that limits the power conversion efficiency (PCE) of perovskite solar cells (PSCs). Light-trapping structures and metal plasmons have been found to enhance light absorption in PSCs, thus improving PCE. In this study, two different types of CH3NH3PbI3 PSCs, incorporating an array of ellipsoidal Ag nanoparticles (NPs) within the active layer and an ITO moth-eye grating on the top surface, were designed. The impact of variations in the shape and position the Ag NPs, as well as the inclusion of the ITO moth-eye grating, on light absorption, was thoroughly investigated. The maximum photocurrent density and PCE reach 25.89 mA/cm2, 23.77% which is 1.24 times larger than that of the planar reference. The combination of embedded Ag NPs and the ITO antireflection layer causes this synergistic effect. These findings have the potential to design and prepare high-efficiency PSCs